The dialysis of Ochratoxin A (OTA) - Malir, F; Severa, J; Roubal, T; Kacerovsky, J; Fixa, P; Moucka, P; Zahradnik, J; Knizek, J; Osterreicher, J; Brndiar, M; Cerna, M (Mycotoxin research, 2001)
Standard dialysis did not result in a decrease of the OTA level in the blood serum of patients regularly treated by dialysis. Therefore, we examined the effect of dialysis on both OTA bound to the blood plasma proteins and free OTA. We carried out an in vivo experiment to determine OTA levels in the serum of patients in the terminal stage of chronic renal insufficiency (CHRI) before and after dialysis and also in the dialysate in which we did not find OTA. OTA bound to blood plasma proteins did not penetrate the dialysis membrane. In contrast, free OTA during an in vitro experiment with the identical dialyzer (as during the in vivo experiment), easily penetrated the same dialysis membrane.